Comparative Analysis of the Accuracy of Six Intraoral Scanners Using a Full-Arch Model - Münir Demirel; Faruk Emir; Gülsüm Ceylan; Almira Ada Diken Türksayar (European Annals of Dental Sciences)

(untitled)
Objective: This in vitro study aimed to evaluate the scan accuracy of 6 intraoral scanners (IOSs) by using a dentate model.Methods: A maxillary dentate reference model was digitized with an industrial-grade blue light optical scanner to generate a reference standard tessellation language (STL) file. The same model was digitized by using 6 IOSs (Trios 4, Trios 3, Primescan, Omnicam, Planmeca Emerald S, and Medit i700) (n=10) to generate test scan STLs. All STL files were imported into a 3-dimensional analysis software program (Geomagic Control X). Test scan STLs were superimposed over the reference STL by using the initial and best-fit alignments of the software program, and the deviations of the scans of IOS from that of the optical scanner were calculated with the root mean square (RMS) method. The average deviation method was used to define the precision of the scans. Kruskal-Wallis and Bonferroni tests were used to statistically evaluate the data (α=0.05).Results: A significant difference was observed between groups in terms of RMS values (p